Retinopathy and stroke recurrence in type 2 diabetes patients and controls - Hjelmgren, Ola (University of Gothenburg, 2018)
The datamaterial consists of 445 patients with type 2 diabetes mellitus and a matched control group of 445 patients without diabetes, who had all suffered their first stroke or TIA.
The aims of the material is to study if retinopathy increases the risk of stroke recurrence in stroke patients with type 2 diabetes. Also, to study if stroke patients with type 2 diabetes have an increased risk of stroke recurrence compared to non-diabetics and if stroke patients with type 2 diabetes, regardless of retinopathy, have a higher incidence of carotid stenosis. Also, to study if stroke patients with type 2 diabetes retinopathy have increased incidence of carotid stenosis.

Datamaterialet består av 445 patienter med typ 2 diabetes och en matchad kontrollgrupp med 445 patienter utan diabetes, som alla har haft stroke eller TIA.
Retinopati och återfall i stroke hos typ 2 diabetespatienter och matchade kontroller
Keywords: Arteriosclerosis; Arterioskleros; DIABETES; DIABETES; HEALTH; HÄLSA; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Medical and Health Sciences; Medicin och hälsovetenskap; Health; Hälsa